ANALISIS PEMETAAN PENILAIAN RESPONDEN TERHADAP ATRIBUT VIDEO PENYULUHAN KOMODITAS CABAI DI DESA TITIAN RESAK KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Febrina Ayuningtyas; Fajar Restuhadi; Deby Kurnia (Universitas Sebelas Maret, 2019)
This research aims to identify the level of farmers ‘interest in 8 types of chili commodity extension videos, as well as identifying and analyzing attributes that affect the appeal of extension videos. The research was conducted in the village of Titian Resak, with consideration of the village is one of the villages that has many farmers and has an active farmers group. The samples in this research were 100 novice and advanced farmers and 12 people in multimedia, extension and communication. This research is a social experiment research by assessing 8 videos about chili cultivation. Sensory analysis is hedonic testing and descriptive testing. Cluster analysis (AHC) of the hedonic test and the PCA analysis of the descriptive test are further analyzed using the preference mapping technique. The results of the research showed the sensory data analysis sourced from the panelists positioning the number 8 video to be a video extension of chili commodities with the highest favorite level of 86% with the average cluster rating of 6.53 (very fond) and has characteristic of the story, transition, audio, narrative, sound effect, back sound, movie, visual, color and duration. The results of this research are as a reference material in aligning relationships